Synthetic Contrasts in Musculoskeletal MRI: A Review. Issue 1 (14th January 2023) - Hilbert, Tom; Omoumi, Patrick; Raudner, Marcus; Kober, Tobias
Abstract: This review summarizes the existing techniques and methods used to generate synthetic contrasts from magnetic resonance imaging data focusing on musculoskeletal magnetic resonance imaging. To that end, the different approaches were categorized into 3 different methodological groups: mathematical image transformation, physics-based, and data-driven approaches. Each group is characterized, followed by examples and a brief overview of their clinical validation, if present. Finally, we will discuss the advantages, disadvantages, and caveats of synthetic contrasts, focusing on the preservation of image information, validation, and aspects of the clinical workflow.